Establishing the Fact of Document Forgery: Modern Realities - T. F. Moiseeva (Теория и практика судебной экспертизы)
The paper examines the problems of forensic forgery detection in digitally manipulated documents. The feasibility of questioned signature identification from document photocopies is also considered.